Scientific and statutory modelling of the participants’ good fatin in tax relations - Pilipenka, Aleksandr A. (Journal of the Belarusian State University. Law, 2020)
The theoretical and practical issues of taxpayer’s good faith are studied. Innovative scientific aspects of fair tax administration are covered. The necessity to give the actions of supervisory authorities a conscientious nature as well as the necessity to enshrine the principle of good faith in tax legislation as applied to all participants in tax relations are grounded.
Keywords: good faith; taxpayer’s good fait; tax benefit; fair tax administration; judicial discretion